â€œLearning Functional Grammar is funâ€: A snapshot of functional grammar unit at an English Education Department in Indonesia - Emi Emilia; J. R. Martin (Indonesian Journal of Applied Linguistics, 2023)
This paper reports on a teaching program for the Functional Grammar (FG) unit at an English Education Study Program of a state university in West Java Indonesia in 2020-2022.Â  Three cohorts of pre-service teachers in semester six were involved in the program (38 students in 2020, 26 in 2021, and 36 in 2022). The teaching program was conducted online due to the Covid 19 pandemic. The report focuses on exploring studentsâ€™ understanding of Systemic Functional Linguistics (SFL) â€“ FG in particular, and their ability to use SFL in text analysis. The studyÂ  also addresses studentsâ€™ opinions on learning SFL through FG unit. TheÂ  study used a qualitative case study design and the data were obtained from participant observations, a questionnaire distributed at the end of the teaching program, and analysis of studentsâ€™ essays on text analyses. In the interest of space, the paper will only present and discuss data from the questionnaire and three samples of student essays. The questionnaire data were analysed qualitatively using a thematic analysis of different aspects of the unit and SFL, and studentsâ€™ essays were analysed using SFL, especially theme, transitivity, and mood systems in lexicogrammar stratum. The data from the questionnaire indicate that all the students in all cohorts responded positively to the teaching program. Many students in each cohort said that learning FG is fun, enjoyable, interesting, and useful for both daily and academic life. They displayed a good understanding of SFL, including its basic principles, notions, and values Â â€“ especially concerning their reading and writing improvement. The data from studentsâ€™ essays also reveal their ability to show how and why the text means what it does and to evaluate why the text is or is not effective for its own purposes. On this basis, it is recommended that SFL be introduced to Indonesian university students to enhance their literacy capacity and to Indonesian teachers to improve their teaching skills and their ways to develop assessment that is linguistically informed.